Effectiveness of Guided Discovery-Based Worksheets to Improve Learning Outcomes in Acid-Base Concept - Ma'firah, Marla; Zainul, Rahadian (Jurnal Pendidikan MIPA, 2022)
This research was conducted to develop students’ worksheets based on guided discovery learning on acid-base materials. This student worksheet will be the basic content for developing a content learning system to improve the learning outcomes of 11th grade high school students in the pandemic era. Research and Development (R&D) using the ADDIE model is the research method used. Based on the research that has been carried out, the validity as measured by the Aiken's V formula is 0.85 which indicates that the developed students’ worksheets are valid. The value of practicality of teachers and students was obtained by 84% and 88% which indicated the very practical category. Then, the N-Gain value obtained is 54.68% which indicates that worksheet is effective in improving student learning outcomes. So it can be concluded that this student worksheet is valid, practical, and effective to be used as a basic content in developing a content learning system based on guided discovery learning on acid and base. Keywords: students’ worksheets, guided discovery, acid-base.  DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1347-1357